Prevalence and distribution of children with congenital heart diseases in the central Anatolian region, Turkey - Başpinar, Osman; Karaaslan, Sevim; Oran, Bülent; Baysal, Tamer; Elmaci, A Midhat; Yorulmaz, Alaaddin (The Turkish Journal of Pediatrics, 2006)
Congenital heart diseases (CHD) are the most frequent malformation at birth. The aims of this study were to assess the prevalence of congenital heart disease, their different types, and the detection rate among children in the central Anatolian region in Turkey. The study was conducted during an eight-year period (March 1995-December 2002). The prevalence of CHD in a large tertiary care hospital in the central Anatolian region in Turkey was studied. The diagnosis of a structural defect was based on echocardiographic study. The following age groups were considered: neonates, infants and toddlers, preschool children, schoolchildren, and adolescents. In the study period, 1,693 children were found to have CHD; 1253 patients were neonates and infants. Total prevalence of CHD over the study period was 7.77 per 1000 live-born. The prevalence increased from 6.35 to 9.65 per 1000 live births between 1995 and 2002 (p < 0.05). The average age at diagnosis was 2.2 +/- 3.64 years (1 day to 18 years, median 5 months). There were 863 (51%) boys and 830 (49%) girls, with a male/female ratio of 1:1. Isolated ventricular septal defect (32.6%) was the most frequent acyanotic anomaly, and tetralogy of Fallot (5.8%) was the most frequent cyanotic anomaly. The commonest non-cardiac anomalies with CHD were musculoskeletal anomalies. Down syndrome was determined in 83 patients (78.3%) from all syndromic CHD cases. Congenital heart disease is a very significant health problem. It requires urgent measures in terms of organization of early diagnosis and proper management. The prevalence rate is comparable to that of similar developed countries. Increasing incidence of CHD might be attributed to more diagnoses with new technologic development or it may indicate a real increase in the defects.